Transcription of interviews with startup founders: East Africa - Mkalama, Benedict Wandera; Ouma, Stefan (Mobile Capital and (Im)Mobile Entrepreneurs: Start-up Success, Institutional Context and the "Laws of Start-up Money" in Silicon Savannah, 2022)
Mkalama, B. and Ouma, S. (2024) ‘To whom does the money go? Mapping the uneven financial geographies of venture capital in ‘Silicon Savannah’, Kenya’, Finance and Space, 1, 517–541. Link: https://doi.org/10.1080/2833115X.2024.2418871 Mkalama, B. and Ouma, S. (2025) ‘Making Sense of Funding Inequalities in the Venture Capital Space: A State-of-the-Art Paper with Views from Africa’, Socio-Economic Review. DOI: 10.1093/ser/mwaf007 Link: https://doi.org/10.1093/ser/mwaf007
Keywords: Economic geography; Social justice; Venture capital; Regional disparities; Gender; Race; Intersectionality (Sociology); Interviews; Startup Founder; Geographic Inequity; Silicon Savannah; Inequality; Entrepreneurial Mobility; Startup Ecosystem; Financial Geography; Structural Barrier; Barriers to Entry (Economic Theory)